Beneficial effects of memantine on ischemia/reperfusion injury following torsion/detorsion induced testicular damage in rats: Improvement in histological and biochemical parameters. Issue 4 (August 2021) - Jafari, Abbas; Ghasemnejad-Berenji, Hojat; Nemati, Mohadeseh; Pashapour, Sarvin; Sadeghpour, Sonia; Ghasemnejad-Berenji, Morteza
Summary: Introduction: Testicular torsion is a common urologic emergency and one of the causes of infertility in males. Hence, prompt diagnosis and treatment are important to prevent testicular damages. It has been reported that memantine, a drug for Alzheimer's disease has anti-oxidative role against cerebral ischemic stroke and cardiac ischemia reperfusion. Objective: In this experimental study, the effects of memantine on a testicular torsion injury in adolescent rat testis after ischemia/reperfusion (I/R) were evaluated. Study design: Thirty-six adolescent rats were divided into three groups with 12 rats per group including sham-operated, T/D (torsion/detorsion) + vehicle, and T/D + memantine (10 mg/kg). Testicular torsion was induced for 2 h by rotating right testis 720 0 in the clockwise direction. In treated group 30 min before detorsion, a single intraperitoneal dose of memantine was administered. After 4 h of reperfusion, orchiectomy was conducted and Histopathological and biochemical evaluations of testicular tissue samples were performed. Results: The malondialdehyde level in the T/D group was significantly greater than in the sham operated group. Moreover, the testicular malondialdehyde values in the T/D + memantine group were significantly lower than in the T/D group. Also, significant decreases occurred in catalase and superoxide dismutase activities in the T/D group compared with sham operated group. These values were significantly greater in the memantine group than in the T/D group. Furthermore, after induction of T/D, histopathological evaluations also revealed severe testicular damages which were improved by memantine administration. Discussion: Memantine prevented increases in oxidative stress markers and reductions of antioxidants during I/R injury in the current study. Subsequently the histologic injury was reduced in rats treated with memantine. The antioxidant characteristics of memantine and its protective effects have been shown in our study. Conclusion: These results suggest that administration of memantine before detorsion prevents I/R cellular damage in testicular torsion. This drug probably acts through reduction of reactive oxygen species and support antioxidant enzyme systems. Summary Figure Administration of memantine before detorsion ameliorates the oxidative stress and decreases the histologic damage that occurs after testicular torsion. Summary Figure